Zirconium and calcium coupled aluminum-based composite coagulant as well as preparation method and application thereof

By introducing zirconium and calcium into the aluminum-based coagulant to form a composite coagulant, the problems of low treatment efficiency of fluorine-containing wastewater and pollutant residues in the prior art are solved, and a more efficient and economical wastewater treatment effect is achieved.

CN119285052AActive Publication Date: 2025-01-10RES CENT FOR ECO ENVIRONMENTAL SCI THE CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411481947.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

In the prior art, when treating fluorine-containing wastewater, the pH of the coagulant has a narrow range of application, low treatment efficiency and easy to produce other pollutants. The use of aluminum-based coagulant alone requires excessive addition, resulting in increased costs and residual metal ions in the effluent. question.

Method used

Using an aluminum-based composite coagulant coupled with zirconium and calcium, a polymorphic mixture is formed through the hydrolysis reaction of aluminum salt, zirconium salt and calcium salt, increasing binding sites and molecular chain length, improving coagulation efficiency, and in a wider range of Maintain good coagulation effect within the pH range.

Benefits of technology

It significantly improves the coagulation efficiency, reduces the amount of aluminum salt, reduces the concentration of aluminum ions in the effluent water, and maintains a good fluorine removal effect under a wider pH range and pollutant concentration, reducing treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285052A_ABST
    Figure CN119285052A_ABST
Patent Text Reader

Abstract

The invention provides a zirconium and calcium coupled aluminum-based composite coagulant as well as a preparation method and application thereof, and belongs to the technical field of environment and chemistry. The preparation method of the zirconium and calcium coupled aluminum-based composite coagulant comprises the following steps: dissolving an aluminum salt in water to obtain an aluminum salt aqueous solution; adding zirconium salt into the aluminum salt aqueous solution according to the molar ratio of aluminum ions to zirconium ions of (5-30): 1, and carrying out first hydrolysis reaction to obtain a polymeric mixture; and according to the molar ratio of the sum of the mole of the aluminum ions and the zirconium ions to the mole of the calcium ions being (1-30): 1, calcium salt is added into the polymeric mixture for a second hydrolysis reaction, and the aluminum-based composite coagulant coupled with the zirconium and the calcium is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environment and chemical technology, and in particular relates to an aluminum-based composite coagulant coupled with zirconium and calcium, and a preparation method and application thereof. Background Art

[0002] With the rapid development of my country's industry, more and more fluorine resources are being applied to modern industries, such as the semiconductor industry, photovoltaic industry, glass manufacturing industry, etc., and more and more fluorine-containing wastewater is generated, and the fluorine concentration in the wastewater gradually increases, and the acidity gradually increases. If these fluorine-containing wastewaters are directly discharged without treatment, they will seriously endanger the surrounding ecological environment and human health. Therefore, those skilled in the art have explored a variety of fluoride removal methods, such as membrane separation, ion exchange, adsorption, and electrochemical methods.

[0003] The membrane separation method has a high removal efficiency for fluoride ions, but it has high requirements for the quality of the influent water, the treatment equipment is prone to pollution and scaling, and the treatment cost is high, so it is not suitable for treating large-scale industrial wastewater. Although the ion exchange method has the characteristics of high defluorination efficiency and simple regeneration, it will produce a large amount of fluorine-loaded waste, which may lead to secondary pollution problems; and the production cost and regeneration cost of the resin used are high, and it is not suitable for treating large-scale industrial wastewater. The adsorption method is mainly affected by adsorption capacity, adsorption efficiency, etc., and is often used to treat wastewater with low fluoride concentration (less than 50 mg / L). The coagulation and sedimentation method has the characteristics of low treatment cost, simple equipment, and easy operation, so it is considered to be the best choice for treating industrial wastewater. Fluoride ions in wastewater can form insoluble substances with a variety of substances, and then the solid phase precipitate is removed from the solution by some means, thereby achieving the purpose of defluorination. However, the pH application range of the coagulants currently available on the market is narrow, and the efficiency is low when used to treat fluoride-containing wastewater, and other pollutants will be generated. Alternatively, excessive amounts of coagulants are added during the treatment of fluoride-containing wastewater, which increases costs and makes it easy for some metal ions in the coagulant to remain in the effluent. Summary of the invention

[0004] In view of the above technical problems, the present invention provides an aluminum-based composite coagulant coupled with zirconium and calcium, and a preparation method and application thereof, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.

[0005] As a first aspect of the present invention, a method for preparing an aluminum-based composite coagulant coupled with zirconium and calcium is provided, comprising: dissolving aluminum salt in water to obtain an aluminum salt aqueous solution; According to the molar ratio of aluminum ion to zirconium ion of 5-30:1, zirconium salt is added to the aluminum salt aqueous solution to carry out a first hydrolysis reaction to obtain a polymeric mixture; According to the molar ratio of the sum of the moles of aluminum ions and zirconium ions to calcium ions being 1-30:1, calcium salt is added to the polymer mixture for a second hydrolysis reaction to obtain an aluminum-based composite coagulant coupled with zirconium and calcium.

[0006] As a second aspect of the present invention, there is provided an aluminum-based composite coagulant coupled with zirconium and calcium, which is prepared by the above method.

[0007] As a third aspect of the present invention, there is provided a use of the above-mentioned aluminum-based composite coagulant coupled with zirconium and calcium in wastewater treatment.

[0008] In the embodiment of the present invention, aluminum salt is dissolved in water, and then zirconium salt is added to the aluminum salt aqueous solution for a first hydrolysis reaction. Through the interaction between the aluminum salt and the zirconium salt, a polymer mixture containing Al-O-Al, Zr-O-Zr and / or Al-O-Zr bonds is formed, so as to provide more binding sites for the coagulant and the pollutants in the wastewater. At the same time, the introduction of zirconium salt promotes the hydrolysis and polymerization of aluminum salt, prompting the aluminum salt to transform into a polymer state such as Al-O-Al, Al-O-Zr, and the H released by the hydrolysis of zirconium salt + It will significantly affect the form of Al in the coagulant. By adding calcium salt to the polymer mixture for a second hydrolysis reaction, Ca is coupled with Al and / or Zr during the hydrolysis process, so that the polymer mixture is converted into a more complex polymer mixture, and an aluminum-based composite coagulant coupled with zirconium and calcium (hereinafter referred to as composite coagulant) is obtained. The preparation method of the composite coagulant provided by the present invention is simple to operate, the process is controllable, suitable for large-scale promotion, and has broad application prospects. Compared with the use of aluminum-based coagulants alone, the composite coagulant provided by the present invention has significantly improved coagulation efficiency. While ensuring an effective coagulation effect, the amount of aluminum salt added can be reduced, so that the concentration of aluminum in the effluent is significantly lower than that of the aluminum-based coagulant added alone. At the same time, compared with single aluminum-based coagulants, zirconium-based coagulants, and calcium-based coagulants, the composite coagulant provided by the present invention can maintain a better coagulation effect in a wider pH range and pollutant concentration range. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 The figure is a treatment effect diagram of fluoride-containing wastewater by Al-Zr composite coagulant in Comparative Examples 1 to 6;

[0010] Figure 2 The fluoride removal effect diagram of the composite coagulant in Examples 1 to 10 in wastewater containing fluoride at a concentration of 10 mg / L;

[0011] Figure 3 The fluorine removal effect diagram of the composite coagulant in Examples 1 to 10 in wastewater containing fluorine at a concentration of 50 mg / L;

[0012] Figure 4It is a graph showing the defluorination effect of the composite coagulant and the AlCl3 coagulant in Example 4, Comparative Example 1, Comparative Example 7, and Comparative Example 8 in wastewater containing fluorine at a concentration of 50 mg / L;

[0013] Figure 5 The fluorine removal effect diagram of the composite coagulant and the AlCl3 coagulant in Example 9, Comparative Example 1, Comparative Example 7, and Comparative Example 8 in wastewater containing fluorine at a concentration of 10 mg / L;

[0014] Figure 6 The fluoride removal effect diagram of the composite coagulant in Example 4, Comparative Example 9 and Comparative Example 10 in wastewater containing fluoride at a concentration of 50 mg / L;

[0015] Figure 7 The treatment effect of the composite coagulant in Example 4 on fluorine-containing wastewater at different dosages;

[0016] Figure 8 This is the treatment effect diagram of fluoride-containing wastewater with AlCl3 coagulant at different dosages;

[0017] Fig. 9 The effect diagram of the composite coagulant in Example 4 on the treatment of fluoride-containing wastewater under different pH conditions;

[0018] Fig.10 This is the treatment effect of AlCl3 coagulant on fluoride-containing wastewater under different pH conditions;

[0019] Fig.11 The treatment effect diagram of the composite coagulant and AlCl3 coagulant on the simulated natural fluoride-containing wastewater in Example 4, Comparative Example 1, Comparative Example 7 and Comparative Example 8;

[0020] Fig.12 This is a graph showing the detection results of the composite coagulant in Example 4 by electrospray ionization mass spectrometry (ESI-MS);

[0021] Fig.13 This is the electrospray ionization mass spectrometry (ESI-MS) detection result diagram of AlCl3 coagulant;

[0022] Fig.14 This is the infrared spectrum of the flocculants in the defluorination process of the composite coagulant and AlCl3 coagulant in Example 4. DETAILED DESCRIPTION

[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0024] There are many problems that need to be solved when treating wastewater with the current coagulation and sedimentation method. For example, when treating fluoride-containing wastewater, most of them form calcium fluoride by adding excessive calcium oxide, but other ions present in the wastewater will affect the formation and precipitation of calcium fluoride. For example, salts such as sodium chloride and sodium sulfate will increase the solubility of calcium fluoride, while salts such as calcium chloride and calcium sulfate will reduce its solubility. Some also use aluminum salt coagulation, but a large amount of aluminum salt coagulant needs to be added, and high concentrations of aluminum ions are likely to remain in the wastewater. Zirconium salts have good biocompatibility and strong fluoride removal capabilities, but they are easy to agglomerate during application, have a narrow pH range of application, and while removing fluoride, they may also have a certain adsorption effect on other ions, resulting in poor selectivity.

[0025] Based on this, the present invention provides an aluminum-based composite coagulant coupled with zirconium and calcium, and a preparation method and application thereof. Zirconium ions and calcium ions are introduced into the aluminum-based coagulant in sequence to promote the conversion of aluminum ions into a polymeric state that is more easily combined with pollutants in wastewater. The prepared composite coagulant can maintain a good coagulation effect in a wider pH range and pollutant concentration range.

[0026] Specifically, as a first aspect of the present invention, a method for preparing an aluminum-based composite coagulant coupled with zirconium and calcium is provided, comprising: dissolving aluminum salt in water to obtain an aluminum salt aqueous solution; According to the molar ratio of aluminum ion to zirconium ion of 5-30:1, zirconium salt is added to the aluminum salt aqueous solution to carry out a first hydrolysis reaction to obtain a polymeric mixture; According to the molar ratio of the sum of the moles of aluminum ions and zirconium ions to calcium ions being 1-30:1, calcium salt is added to the polymer mixture for a second hydrolysis reaction to obtain an aluminum-based composite coagulant coupled with zirconium and calcium.

[0027] In the embodiment of the present invention, aluminum salt is dissolved in water, and then zirconium salt is added to the aluminum salt aqueous solution for a first hydrolysis reaction. Through the interaction between the aluminum salt and the zirconium salt, a polymer mixture containing Al-O-Al, Zr-O-Zr and / or Al-O-Zr bonds is formed, so as to provide more binding sites for the coagulant and the pollutants in the wastewater. At the same time, the introduction of zirconium salt promotes the hydrolysis and polymerization of aluminum salt, prompting the aluminum salt to transform into a polymer state such as Al-O-Al, Al-O-Zr, and the H released by the hydrolysis of zirconium salt +The form of Al in the coagulant will be significantly affected. By adding calcium salt to the polymer mixture for a second hydrolysis reaction, Ca is coupled with Al and / or Zr during the hydrolysis process, so that the polymer mixture is converted into a more complex polymer mixture, and an aluminum-based composite coagulant coupled with zirconium and calcium (hereinafter referred to as composite coagulant) is obtained. The preparation method of the composite coagulant provided by the present invention is simple to operate, has a controllable process, is suitable for large-scale promotion, and has broad application prospects.

[0028] In the embodiment of the present invention, after adding aluminum salt to water, adding zirconium salt to aluminum salt aqueous solution, and adding calcium salt to the polymer mixture, stirring is performed for 0.5-1.5 hours to allow aluminum ions, zirconium ions, and calcium ions to undergo hydrolysis and polymerization. + The morphology of aluminum ions in the composite coagulant is significantly affected. Excessive zirconium salt content will result in the precipitation of aluminum hydroxide and zirconium hydroxide after the addition of water-soluble zirconium salt, which is not conducive to the formation of a polymer mixture. Changing the order of adding zirconium salt and calcium salt, or adding aluminum salt, zirconium salt and calcium salt at the same time, insoluble aluminum hydroxide, zirconium hydroxide, calcium hydroxide and other granular substances will be quickly formed, and a composite coagulant cannot be formed. This shows that adding aluminum salt, zirconium salt and calcium salt in sequence to gradually hydrolyze them makes it easier to control their transformation into a polymer mixture and a more complex polymer mixture.

[0029] According to an embodiment of the present invention, the above method also includes: aging the aluminum-based composite coagulant coupled with zirconium and calcium, wherein the aging time is 24-72 hours. During the aging process, the hydrolysis reaction between aluminum ions, zirconium ions and calcium ions is further promoted to transform them into a more complex polymer mixture, and it is helpful to disperse and suspend the composite coagulant in water, thereby improving its coagulation effect. Furthermore, with the extension of the aging time, the coagulation effect will gradually improve. However, when the aging time reaches 72 hours, the coagulation effect of the composite coagulant will decrease. This is because an excessively long aging time will cause the aluminum ions, zirconium ions, and calcium ions in the composite coagulant to be transformed into aluminum hydroxide, zirconium hydroxide, and calcium hydroxide precipitates, thereby affecting its coagulation effect.

[0030] According to an embodiment of the present invention, the aluminum salt includes any one of aluminum chloride and aluminum sulfate, the zirconium salt includes any one of zirconium chloride and zirconium sulfate, and the calcium salt includes any one of calcium chloride and calcium sulfate. Chloride ions and sulfate ions have little influence on the hydrolysis of aluminum ions, zirconium ions and calcium ions. At the same time, it is also necessary to consider whether other impurities will be introduced into the effluent. It should be noted that the present invention only provides two optional anion types, and other water-soluble aluminum salts, zirconium salts, and calcium salts can also be selected as long as the anion types that do not affect the hydrolysis effect of aluminum ions, zirconium ions, and calcium ions.

[0031] As a second aspect of the present invention, there is provided an aluminum-based composite coagulant coupled with zirconium and calcium, which is prepared by the above method.

[0032] According to an embodiment of the present invention, the aluminum-based composite coagulant coupled with zirconium and calcium is a colorless, clear and transparent solution.

[0033] As a third aspect of the present invention, there is provided a use of the above-mentioned aluminum-based composite coagulant coupled with zirconium and calcium in wastewater treatment.

[0034] In an embodiment of the present invention, the composite coagulant provided by the present invention has a significantly improved coagulation efficiency compared with the single use of aluminum-based coagulant. Under the condition of ensuring an effective coagulation effect, the dosage of aluminum salt can be reduced, so that the concentration of aluminum ions in the effluent is significantly reduced compared with the single addition of aluminum-based coagulant. This is because, in the first hydrolysis reaction process, aluminum ions and zirconium ions undergo hydrolysis polymerization to form compounds with Al-O-Al, Zr-O-Zr and / or Al-O-Zr bonds. The introduction of zirconium ions further promotes the hydrolysis polymerization of aluminum ions, prompting aluminum ions to transform into a polymeric state that is more easily combined with pollutants in wastewater. In the second hydrolysis reaction process, calcium ions are introduced, and calcium ions also undergo hydrolysis polymerization, further reacting with compounds with Al-O-Al, Zr-O-Zr and / or Al-O-Zr bonds, so that the molecular weight of the hydrolyzate increases and the molecular chain becomes longer, forming a more complex polymeric mixture, increasing the binding sites with pollutants in wastewater, and producing larger floccules in the coagulation process, which can shorten the sedimentation time and improve the coagulation effect of the composite coagulant.

[0035] According to an embodiment of the present invention, the above-mentioned wastewater includes fluoride-containing wastewater and fluoride-containing groundwater. The pH of the wastewater is 2-10, preferably 4-9, and more preferably 4-6. The concentration of fluorine in the wastewater is 1-70 mg / L, preferably 10-50 mg / L. Compared with a single aluminum-based coagulant (applicable to wastewater treatment with a pH of 5-7), a zirconium-based coagulant (applicable to wastewater treatment with a pH of 2-4), and a calcium-based coagulant (applicable to wastewater treatment with a pH of 7-8), the composite coagulant provided by the present invention can maintain a good defluorination effect in a wider pH range. Since calcium ions have a common ion effect, the solubility of insoluble precipitates can be reduced, making it easier to precipitate the flocculants produced by the composite coagulant, thereby having a higher defluorination effect under a wider fluoride concentration.

[0036] According to an embodiment of the present invention, when the concentration of fluorine in wastewater is 1-30 mg / L, the molar ratio of aluminum ions to zirconium ions in the aluminum-based composite coagulant coupled with zirconium and calcium (i.e., n Al / n Zr ) is 5:1, the molar ratio of the sum of the moles of aluminum ions and zirconium ions to the molar ratio of calcium ions (i.e. (n Al +n Zr / n Ca )) is 25:1; when the concentration of fluorine in wastewater is 30-70 mg / L, the molar ratio of aluminum ions to zirconium ions in the aluminum-based composite coagulant coupled with zirconium and calcium is 5:1, and the molar ratio of the sum of the moles of aluminum ions and zirconium ions to calcium ions is 4:1. The molar ratio of aluminum ions to zirconium ions is preferably 5:1. Under the preferred molar ratio of aluminum ions to zirconium ions, the polymer mixture formed by aluminum ions and zirconium ions has the best morphology and is more conducive to the subsequent complexation with calcium ions.

[0037] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.

[0038] In order to explore the effect of the molar ratio of aluminum ions to zirconium ions on the fluoride removal effect of the composite coagulant, the present invention prepared aluminum-zirconium composite coagulants (Al-Zr composite coagulants) of Comparative Examples 1 to 6.

[0039] Comparative Example 1

[0040] In the Al-Zr composite coagulant of this comparative example 1, the water-soluble aluminum salt is aluminum chloride hexahydrate, and the water-soluble zirconium salt is zirconium chloride. The molar ratio of aluminum chloride hexahydrate to zirconium chloride is 5:1. The specific preparation method is as follows.

[0041] Weigh 2.4143 g of aluminum chloride hexahydrate and dissolve it in 100 ml of ultrapure water, stir for 1 hour, and obtain an aluminum chloride aqueous solution; add zirconium chloride to the aluminum chloride aqueous solution, stir for 1 hour, and obtain a first mixed solution; mature the first mixed solution for 48 hours to obtain the Al-Zr composite coagulant of Comparative Example 1.

[0042] Comparative Example 2-Comparative Example 6

[0043] The molar ratios of aluminum chloride hexahydrate and zirconium chloride in the Al-Zr composite coagulants of Comparative Examples 2 to 6 are 10:1, 15:1, 20:1, 25:1, and 30:1, respectively, and the specific preparation methods are the same as those of Comparative Example 1.

[0044] Furthermore, the Al-Zr composite coagulants in Comparative Examples 1 to 6 were applied to wastewater with a fluorine concentration of 10 mg / L to investigate the fluorine removal effect, wherein the addition amount of the composite coagulant was 0.5 mmol / L.

[0045] Figure 1This is a diagram showing the treatment effect of the Al-Zr composite coagulant on fluoride-containing wastewater in Comparative Examples 1 to 6.

[0046] Depend on Figure 1 It can be seen that with the increase of the molar ratio of aluminum chloride hexahydrate and zirconium chloride, the fluoride removal effect also increases, and when the molar ratio of aluminum chloride hexahydrate and zirconium chloride is 5:1, the fluoride ion removal rate reaches the highest. Since the Al-Zr composite coagulant with a molar ratio of aluminum chloride hexahydrate and zirconium chloride below 5:1 cannot be successfully prepared (a large amount of aluminum hydroxide and zirconium hydroxide precipitates are produced when zirconium salt is added to the aluminum salt aqueous solution), when preparing the calcium-containing composite coagulant, the molar ratio of aluminum chloride hexahydrate and zirconium chloride is fixed at 5:1, and a series of composite coagulants with different calcium content ratios are prepared to explore the fluoride removal ability of multiple metal ion composites.

[0047] In order to explore the effect of the proportion of calcium ions on the fluoride removal effect of the composite coagulant, the present invention prepared the composite coagulants of Examples 1 to 10.

[0048] Example 1

[0049] In the composite coagulant of this embodiment 1, the water-soluble aluminum salt is aluminum chloride hexahydrate, the water-soluble zirconium salt is zirconium chloride, and the water-soluble calcium salt is calcium chloride. The molar ratio of aluminum chloride hexahydrate to zirconium chloride is 5:1, and the molar sum of aluminum chloride hexahydrate and zirconium chloride to the molar ratio of calcium chloride is 1:1. The specific preparation method is as follows.

[0050] 2.4143 g of aluminum chloride hexahydrate was weighed and dissolved in 100 ml of ultrapure water, and stirred for 1 hour to obtain an aluminum chloride aqueous solution; zirconium chloride was added to the aluminum chloride aqueous solution and stirred for 1 hour to obtain a first mixed solution; calcium chloride was added to the first mixed solution and stirred for 1 hour to obtain a second mixed solution; the second mixed solution was aged for 48 hours to obtain the composite coagulant of Example 1.

[0051] Example 2-Example 10

[0052] The molar ratio of aluminum chloride hexahydrate to zirconium chloride in the composite coagulants of Examples 2 to 10 is 5:1, and the molar ratio of the sum of the moles of aluminum chloride hexahydrate and zirconium chloride to calcium chloride is 2:1, 3:1, 4:1, 5:1, 10:1, 15:1, 20:1, 25:1, and 30:1, respectively. The specific preparation method is the same as that of Example 1.

[0053] Furthermore, the composite coagulants in Examples 1 to 10 were respectively applied to wastewater with fluoride concentrations of 10 mg / L and 50 mg / L to investigate their fluoride removal effects, wherein the addition amount of the composite coagulant was 0.5 mmol / L.

[0054] Figure 2The fluoride removal effect diagram of the composite coagulant in Examples 1 to 10 in wastewater containing fluoride at a concentration of 10 mg / L; Figure 3 This is a diagram showing the fluoride removal effect of the composite coagulant in Examples 1 to 10 in wastewater containing a fluoride concentration of 50 mg / L.

[0055] Depend on Figure 2 It can be seen that when treating low-concentration fluoride-containing wastewater (10 mg / L), the composite coagulant in Example 9 has the highest removal efficiency for fluoride ions, which is better than composite coagulants with other proportions. Figure 3 It can be seen that when treating high-concentration fluoride-containing wastewater (50 mg / L), the removal efficiency of fluoride ions by the composite coagulant in Example 4 reached the highest, which was better than that of composite coagulants in other proportions.

[0056] In order to explore the effect of composite coagulants containing only aluminum salt and calcium salt and zirconium salt and calcium salt on the fluoride removal effect, the present invention prepared an aluminum-calcium composite coagulant (Al-Ca composite coagulant) of Comparative Example 7 and a zirconium-calcium composite coagulant (Zr-Ca composite coagulant) of Comparative Example 8.

[0057] Comparative Example 7

[0058] In this comparative example 7, an Al-Ca composite coagulant having a molar ratio of aluminum chloride hexahydrate to calcium chloride of 4:1 was prepared, and the specific preparation method is as follows.

[0059] Weigh 2.4143 g of aluminum chloride hexahydrate and dissolve it in 100 ml of ultrapure water, stir for 1 hour, and obtain an aluminum chloride aqueous solution; add calcium chloride to the aluminum chloride aqueous solution, stir for 1 hour, and then mature for 48 hours to obtain the Al-Ca composite coagulant of Comparative Example 7.

[0060] Comparative Example 8

[0061] In this comparative example 8, a Zr-Ca composite coagulant having a molar ratio of zirconium chloride to calcium chloride of 4:1 was prepared. The specific preparation method is as follows.

[0062] Weigh 2.3304 g of zirconium chloride and dissolve it in 100 ml of ultrapure water, stir for 1 hour, and obtain a zirconium chloride aqueous solution; add calcium chloride to the zirconium chloride aqueous solution, stir for 1 hour, and then mature for 48 hours to obtain the Zr-Ca composite coagulant of Comparative Example 8.

[0063] Furthermore, the composite coagulant in Example 4 and the AlCl3 coagulant and the composite coagulants in Comparative Example 1, Comparative Example 7 and Comparative Example 8 were applied to wastewater with a fluorine concentration of 50 mg / L, and the composite coagulant in Example 9 and the AlCl3 coagulant and the composite coagulants in Comparative Example 1, Comparative Example 7 and Comparative Example 8 were applied to wastewater with a fluorine concentration of 10 mg / L to investigate their fluoride removal effects, wherein the amount of the composite coagulant added was 0.5 mmol / L.

[0064] Figure 4 It is a graph showing the defluorination effect of the composite coagulant and the AlCl3 coagulant in Example 4, Comparative Example 1, Comparative Example 7, and Comparative Example 8 in wastewater containing fluorine at a concentration of 50 mg / L; Figure 5 It is a diagram showing the fluorine removal effect of the composite coagulant and the AlCl3 coagulant in Example 9, Comparative Example 1, Comparative Example 7, and Comparative Example 8 in wastewater containing fluorine at a concentration of 10 mg / L.

[0065] Depend on Figure 4 It can be seen that when treating high-concentration fluoride-containing wastewater (50 mg / L), the composite coagulant has a more obvious improvement in the removal efficiency of fluoride ions compared with the AlCl3 coagulant. The composite coagulant in Example 4 has the highest removal efficiency of fluoride ions, with a removal rate of 70.8%. The removal efficiency of fluoride ions by the AlCl3 coagulant is only 50.6%, which is an increase of 20.2%. Figure 5 It can be seen that when treating low-concentration fluoride-containing wastewater (10 mg / L), the removal effect of the composite coagulant on fluoride ions is significantly improved compared with the AlCl3 coagulant. It can be seen that the addition of zirconium chloride can improve the removal efficiency of fluoride ions. The removal efficiency of the composite coagulant on fluoride ions in Example 9 reached the highest, with a removal rate of 83%.

[0066] In order to explore the effect of the addition order of aluminum salt, zirconium salt and calcium salt on the fluoride removal effect of the composite coagulant, the present invention prepared an aluminum-calcium-zirconium composite coagulant (Al-Ca-Zr composite coagulant) of Comparative Example 9 and a calcium-zirconium-aluminum composite coagulant (Zr-Ca-Al composite coagulant) of Comparative Example 10.

[0067] Comparative Example 9

[0068] In this comparative example 9, an Al-Ca-Zr composite coagulant is prepared. The specific preparation method is the same as that in Example 4, except that the order of adding the aluminum salt, the zirconium salt and the calcium salt is to first add the aluminum salt, then add the calcium salt, and finally add the zirconium salt.

[0069] Comparative Example 10

[0070] In this comparative example 10, a Zr-Ca-Al composite coagulant is prepared. The specific preparation method is the same as that in Example 4, except that the order of adding the aluminum salt, the zirconium salt and the calcium salt is to first add the calcium salt, then add the zirconium salt, and finally add the aluminum salt.

[0071] Furthermore, the composite coagulant in Example 4 and the composite coagulants in Comparative Examples 9 and 10 were applied to wastewater with a fluorine concentration of 50 mg / L to investigate the fluoride removal effect, wherein the addition amount of the composite coagulant was 0.5 mmol / L.

[0072] Figure 6This is a diagram showing the fluoride removal effect of the composite coagulant in Example 4, Comparative Example 9, and Comparative Example 10 in wastewater containing fluoride at a concentration of 50 mg / L.

[0073] Depend on Figure 6 It can be seen that the order of adding aluminum salt, zirconium salt and calcium salt will affect the metal form of the coagulant during the polymerization process, thus leading to differences in the coagulation and fluoride removal effect. If aluminum salt is added first and then zirconium salt is added, on the one hand, it can promote the aluminum salt to generate highly polymerized aluminum, and the formed polymeric mixture is also more conducive to complexing with fluoride ions. Then calcium salt is added to further enhance the binding ability of the composite coagulant with fluoride ions. On the contrary, if zirconium salt is added first, because it is easier to hydrolyze, the zirconium salt after rapid hydrolysis is not conducive to complexing with aluminum salt, and at the same time, the optimization effect on the hydrolysis form of aluminum salt itself is also weakened, which is not conducive to the generation of a polymeric mixture that is more conducive to complexing with fluoride ions, nor is it conducive to further complexing with subsequent calcium ions. Calcium salts are also not conducive to the formation of a dominant form that is easier to complex fluoride ions because of the strong alkalinity of their hydrolysis products. Therefore, after the aluminum salt and zirconium salt are compounded, adding calcium salt can weaken the adverse effect of calcium ions on the form of aluminum ions, generate a composite coagulant with a strong ability to complex with fluoride ions, and thus enhance the coagulation effect of the composite coagulant.

[0074] In order to explore the effect of the dosage of the composite coagulant on the fluoride removal effect, the composite coagulant and AlCl3 coagulant in Example 4 were applied to wastewater with a fluoride concentration of 50 mg / L at different dosages.

[0075] Figure 7 The treatment effect of the composite coagulant in Example 4 on fluorine-containing wastewater at different dosages; Figure 8 This is a diagram showing the treatment effect of AlCl3 coagulant on fluoride-containing wastewater at different dosages.

[0076] Depend on Figure 7 and Figure 8 It can be seen that with the continuous increase in the dosage of composite coagulant, the removal efficiency of fluoride ions also increases. When the dosage is 10mmol / L, the removal efficiency of fluoride ions by the composite coagulant reaches 85%, and when the dosage is 14mmol / L, the removal efficiency of fluoride ions reaches 99%. AlCl3 coagulant also shows the same trend, but at the same dosage, the composite coagulant has a better defluorination effect than AlCl3 coagulant.

[0077] In order to explore the effect of pH value of fluorine-containing wastewater on fluoride removal effect, the composite coagulant and AlCl3 coagulant in Example 4 were respectively applied to wastewater with fluoride concentration of 50 mg / L at different pH values, wherein the addition amount of the composite coagulant was 0.5 mmol / L.

[0078] Fig. 9 The effect diagram of the composite coagulant in Example 4 on the treatment of fluoride-containing wastewater under different pH conditions; Fig.10 This is a diagram showing the effect of AlCl3 coagulant on fluoride-containing wastewater treatment under different pH conditions.

[0079] Depend on Fig. 9 and Fig.10 It can be seen that under alkaline conditions (pH>7), the treatment effects of composite coagulants and AlCl3 coagulants on fluoride-containing wastewater are poor, while under acidic conditions (pH<7), the treatment effects of composite coagulants and AlCl3 coagulants on fluoride-containing wastewater are better, but the composite coagulant is better than the traditional AlCl3 coagulant in the pH range of 4-9. As the pH decreases, the removal rate gradually increases. At pH 4, the removal effect of the composite coagulant reaches the best, with a residual fluoride ion concentration of 7.2 mg / L and a removal rate of 85.6%. It can be seen that the composite coagulant is much better at removing fluoride ions under acidic conditions than under alkaline conditions.

[0080] In order to better simulate the fluoride-containing wastewater in nature, tap water was used to prepare simulated wastewater, in which the fluoride ion was 50 mg / L, COD = 20 mg / L, SO4 2- =190 mg / L, the composite coagulant and AlCl3 coagulant in Example 4, Comparative Example 1, Comparative Example 7 and Comparative Example 8 were applied to the treatment of fluorine-containing wastewater, wherein the addition amount of the composite coagulant was 0.5 mmol / L.

[0081] Fig.11 The diagram shows the treatment effects of the composite coagulant and AlCl3 coagulant in Example 4, Comparative Example 1, Comparative Example 7 and Comparative Example 8 on simulated natural fluoride-containing wastewater.

[0082] Depend on Fig.11 It can be seen that when the fluoride concentration is 50mg / L, COD concentration is 20mg / L, SO4 2- When the concentration of wastewater is 190 mg / L, the composite coagulant in Example 4 has the best treatment effect, which is 7% higher than that of using AlCl3 coagulant alone. The composite coagulant in Comparative Example 8 has the worst treatment effect, with a removal rate of only 42.8%. The treatment effect of the composite coagulant in Example 4 is lower than that of the wastewater containing only fluoride ions, because the pH value of the wastewater solution is high and SO4 2- It has a certain inhibitory effect on fluoride removal, resulting in a decrease in the fluoride removal effect of the composite coagulant.

[0083] In order to detect the form of aluminum in the composite coagulant, the composite coagulant and AlCl3 coagulant in Example 4 were detected by electrospray ionization mass spectrometry (ESI-MS).

[0084] Fig.12 This is a graph showing the detection results of the composite coagulant in Example 4 by electrospray ionization mass spectrometry (ESI-MS); Fig.13This is the electrospray ionization mass spectrometry (ESI-MS) detection result of AlCl3 coagulant.

[0085] Depend on Fig.12 and Fig.13 It can be seen that the form of aluminum in the composite coagulant and AlCl3 coagulant is mainly monomer aluminum. The strength of monomer aluminum in the composite coagulant is weaker than that of AlCl3 coagulant, but the total Al in the composite coagulant is 13 The relative strength is 2.28%, which is higher than the total AlCl3 coagulant 13 Therefore, the excellent coagulation effect of the composite coagulant is not only due to the coupling effect of multiple metals, but also because the multi-metal composite significantly affects the hydrolysis process of aluminum ions, so that the composite coagulant shows a stronger defluorination effect than the AlCl3 coagulant.

[0086] In order to detect how the composite coagulant works in the defluorination process, the flocculants in the defluorination process of the composite coagulant and AlCl3 coagulant in Example 4 were tested by infrared spectroscopy (FTIR).

[0087] Fig.14 This is the infrared spectrum of the flocculants in the defluorination process of the composite coagulant and AlCl3 coagulant in Example 4.

[0088] Depend on Fig.14 It can be seen that 980cm -1 The characteristic peak at 605cm is due to the vibration of M (Al / Zr / Ca)-O. -1 The characteristic peak at 3500cm is caused by the vibration of OM (Al / Zr / Ca)-O bond. It can be seen that the peak intensity is significantly enhanced in the composite coagulant. On the one hand, Zr and Ca promote the polymerization of Al, and on the other hand, it is also due to the formation of multiple metal bonds of Al-O-Zr, Zr-O-Ca, and Al-O-Ca. -1 The stretching vibration of -OH bond and the bending vibration caused by the adsorption of HOH groups of water bound intermolecularly were observed, which proved that there were a large number of hydroxyl polymers in the flocculants. By comparing the infrared spectra of the two flocculants, it was found that compared with AlCl3, the 750-1000cm -1 The peak intensity and peak area in the region are larger, which is due to the vibration of Zr-O bond and Zr-F bond caused by the addition of zirconium ions. This shows that zirconium ions are also involved in the process of fluoride removal, and the peak area and peak intensity of -OH in the composite coagulant are higher than those of AlCl3, which is due to the hydrolysis and polymerization of zirconium ions themselves, and the hydrolysis and polymerization of aluminum ions promoted by zirconium ions.

[0089] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum-based composite coagulant coupled with zirconium and calcium, comprising: dissolving aluminum salt in water to obtain an aluminum salt aqueous solution; According to the molar ratio of aluminum ion to zirconium ion of 5-30:1, zirconium salt is added to the aluminum salt aqueous solution to carry out a first hydrolysis reaction to obtain a polymeric mixture; According to the molar ratio of the sum of the moles of aluminum ions and zirconium ions to calcium ions being 1-30:1, calcium salt is added to the polymer mixture to carry out a second hydrolysis reaction to obtain an aluminum-based composite coagulant coupled with zirconium and calcium.

2. The method according to claim 1, further comprising: Ripening the obtained aluminum-based composite coagulant coupled with zirconium and calcium; Wherein, the ripening time is 24-72h.

3. The method according to claim 1, wherein: The aluminum salt includes any one of aluminum chloride and aluminum sulfate, the zirconium salt includes any one of zirconium chloride and zirconium sulfate, and the calcium salt includes any one of calcium chloride and calcium sulfate.

4. The method according to claim 1, wherein: The polymeric mixture includes compounds having Al-O-Al, Zr-O-Zr and / or Al-O-Zr bonds.

5. An aluminum-based composite coagulant coupled with zirconium and calcium, prepared by the method described in any one of claims 1 to 4.

6. Use of the aluminum-based composite coagulant coupled with zirconium and calcium as claimed in claim 5 in wastewater treatment.

7. The use according to claim 6, wherein: The wastewater includes fluoride-containing wastewater and fluoride-containing groundwater.

8. The use according to claim 7, wherein: The pH of the wastewater is 2-10.

9. The use according to claim 7, wherein: The fluorine concentration in the wastewater is 1-70 mg / L.

10. The use according to claim 9, wherein: When the concentration of fluorine in the wastewater is 1-30 mg / L, the molar ratio of aluminum ions to zirconium ions in the aluminum-based composite coagulant coupled with zirconium and calcium is 5:1, and the molar ratio of the sum of the moles of aluminum ions and zirconium ions to calcium ions is 25:1; or When the fluorine concentration in the wastewater is 30-70 mg / L, the molar ratio of aluminum ions to zirconium ions in the aluminum-based composite coagulant coupled with zirconium and calcium is 5:1, and the molar ratio of the sum of the moles of aluminum ions and zirconium ions to calcium ions is 4:1.

Citation Information

Patent Citations

  • Preparation method of polymeric zirconium aluminum chloride inorganic high-efficiency flocculant

    CN108128864A

  • Inorganic calcium-containing composite coagulant and preparation method thereof

    CN115974245A

  • Aluminium chloride containing compositions

    GB0101556D0

  • Fluorine-containing wastewater treatment method

    JP2005131532A

  • A method for producing an iodine-containing aqueous solution using an inorganic flocculant that selectively removes fluoride ions and phosphate ions

    JP7295324B1